2019
DOI: 10.3390/jcm8060786
|View full text |Cite
|
Sign up to set email alerts
|

Risks Related to the Use of Non-Steroidal Anti-Inflammatory Drugs in Community-Acquired Pneumonia in Adult and Pediatric Patients

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used to alleviate symptoms during community-acquired pneumonia (CAP), while neither clinical data nor guidelines encourage this use. Experimental data suggest that NSAIDs impair neutrophil intrinsic functions, their recruitment to the inflammatory site, and the resolution of inflammatory processes after acute pulmonary bacterial challenge. During CAP, numerous observational data collected in hospitalized children, hospitalized adults, and adults admit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
116
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 51 publications
(65 reference statements)
0
116
0
5
Order By: Relevance
“…While no causal evidence of adverse outcomes with NSAIDs in the management of COVID-19 have been published, there are well known risks of non-steroidal anti-inflammatory agents including cardiovascular, gastrointestinal and renal adverse events [64,65]. In the setting of bacterial pneumonia, NSAIDs may impair recruitment of polymorphonuclear cells, resulting in a delayed inflammatory response and resolution of infection, however a causal relationship has not been established [66,67]. RCTs are needed to better understand the safety of NSAIDS in the management of patients with COVID-19.…”
Section: Remdesivirmentioning
confidence: 99%
“…While no causal evidence of adverse outcomes with NSAIDs in the management of COVID-19 have been published, there are well known risks of non-steroidal anti-inflammatory agents including cardiovascular, gastrointestinal and renal adverse events [64,65]. In the setting of bacterial pneumonia, NSAIDs may impair recruitment of polymorphonuclear cells, resulting in a delayed inflammatory response and resolution of infection, however a causal relationship has not been established [66,67]. RCTs are needed to better understand the safety of NSAIDS in the management of patients with COVID-19.…”
Section: Remdesivirmentioning
confidence: 99%
“…This is largely based on data regarding other respiratory infections. 61,63 The primary mechanism through which NSAIDs are hypothesized to impact COVID-19-positive patients is through inhibition of cyclooxygenases. 63 However, there remains no evidence that NSAIDs worsen disease outcomes in COVID-19 patients.…”
Section: Postpartum Nsaid Use For Puis or Covid-19-positive Patientsmentioning
confidence: 99%
“…61,63 The primary mechanism through which NSAIDs are hypothesized to impact COVID-19-positive patients is through inhibition of cyclooxygenases. 63 However, there remains no evidence that NSAIDs worsen disease outcomes in COVID-19 patients. 61,62,64,65 Further, some studies have actually suggested a benefit to NSAID use.…”
Section: Postpartum Nsaid Use For Puis or Covid-19-positive Patientsmentioning
confidence: 99%
“…Relevant to the study of COVID-19, this has previously been shown to be a particular concern in the association between recent use of NSAIDs and pneumonia complications. 16,17 Similar patterns could be hypothesised for, for example, other analgesics, antibiotics, and inhaled glucocorticoids.…”
Section: Consideration #5: How To Define Exposure?mentioning
confidence: 60%